An alpha-glucoside of 1,4-dideoxy-1,4-imino-D-lyxitol with an eleven carbon side chain - Kato, A; Hollinshead, J; Yamashita, Y; Nakagawa, S; Koike, Y; Adachi, I; Yu, C; Fleet, G; Nash, R (2010)
The distribution of pyrrolidine-type iminosugars with a long-side chain appears to be restricted to the relatively unrelated plant families Moraceae, Campanulaceae, and Hyacinthaceae. In a search for glycosidase inhibitors in these plant families, we isolated the 1,4-dideoxy-1,4-imino-d-lyxitol (DIL) glucoside bearing the 1,2,11-trihydroxyundec-4-ene side chain at the C-1α position from the roots of Adenophora triphylla. This iminosugar was a powerful and selective inhibitor of coffee bean α-galactosidase, with an IC 50 value of 8 μM. © 2010 Phytochemical Society of Europe.